Fully Glazed Façade Conception for a Villa with special and Big Size Glass Panels - Raul Corrales Marcos (Challenging Glass Conference, 2018)
The aim of this paper is to explain how the design intent of a bespoke glazed façade develops from the point of view of the façade consultant BIFF SA. The explanation of this concept development is not only interesting because of the different phases of the process, but also because of the unusual specifications and demands established by the architects and the Client, and for the project evolution trough several technical solutions up to final project state. During the concept development materials like stone, steel, aluminum or fabric are normally combined with glass. This challenging glazed façade has been developed for a luxury villa in Switzerland where a triple laminated glass cladding has been selected as the final most suitable solution for creating a building envelope with glass panes of 3000mm W x 7000mm H bonded to a back frame with structural silicone. These units have obviously aesthetic requirements and also different functional applications and the solution should fulfill all demands and do not  the technical aspects of building up a façade with such a big glass units.